Different levels of adoption of buffalo husbandry practices among farmers of different leveis of social participation - YADAV, B L; YADAV, M C (The Indian Journal of Animal Sciences, 2013)
Social participation has highly strong association with the level of adoption of housing (24.83**). feeding (24.36**). breeding (20.54**), disease prevention (45.67**) and sale-purchase (27.53 ** ) practices. The KI increased with increased level of social participation. The ButTalo Management Index (BMI) also increased with increased level of social participation. The BMI in different categories were 67.5.1. 69.80,72.01 and 77.78 in no, low. medium and high level of social participation. The age at first calving (AFC) significantly decreased (P< 0.05) with increased level of participation. The AFC and calving interval (CI) were lowest in butfaloes of respondents of high social participation.